Rola jakości w kształtowaniu lojalności nabywców ubezpieczeń na życie typu unit-linked - Ostrowska, Anna (The Role of Quality in Creating Customers Loyalty of the Unit-Linked Insurance, 2008)
The article discusses the essence of the quality from the point of view of the insurance company and its clients of the life insurance connected with capital fund. The author also presents the role of the quality in the influence upon the client's satisfaction measured by the level of his needs fulfilled, the final estimation of the product, and by the intention to buy the same policy in the same insurance company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 312-319